Konsep Kehidupan Dalam Ruang Pada Kelenteng Sam Kouw Di Surakarta Studi Kasus : Kelenteng T’ien Kok Sie, Kelenteng Poo An Kiong Dan Cetiya Ksiti Garbha - Dyah Susilowati Pradnya Paramita (Dinamika Rekayasa, 2008)
The kelenteng was used by three traditional religions brought by Chinese traders, namely Tao, Khonghucu and Buddhism which then together named Sam Kouw (Tri Darma) The kelenteng Sam Kouw had many worshiped sculptures to which their worship ritualwas based. The kelenteng was taken care by a suhu acted as a mediator during the worship. Due to his role in worship, the Suhu and his family also stayed in the kelenteng.Based on that phenomenon, this research is focused on the rooms usage in kelenteng as a place of interaction of both worship and household routines. This research applies naturalistic qualitative methodology. The researcher played as the main instrument in collecting the data by observation, interview. The data gained during the research was formulated to some topics analyzed inductively before the researcher conducted an inter -topic dialog.. Thi s researched was conducted in three objects with cross sectional method to strengthen the data and sharpen the focus of observation. The three objects are: 1) Kelenteng T’ien Kok Sie in Ketandan; 2) Kelenteng Poo An Kiong in Coyudan, and 3) Cetiya Ksiti Garbha in Srambatan  The result of the research shows that kelenteng Sam Kouw has a public worship room in front of kelenteng , has a particular worship room in behind of kelenteng , and always has a meditation room that has always perpendicular a prominent god altar.